A toughened and scratch-resistant polypropylene composite material
By introducing modified nano-silica carbide into polypropylene composite materials, the problem of insufficient scratch resistance of polypropylene materials has been solved, and the mechanical properties and scratch resistance of the materials have been significantly improved.
Patent Information
- Application Number
- CN202411638654.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing polypropylene materials have relatively poor scratch resistance, limiting their application in certain special areas.
By introducing modified nano-silica carbide into polypropylene composite materials, and improving its dispersion and compatibility in polypropylene through modification treatment, the mechanical properties and scratch resistance of the material are enhanced.
It significantly improves the resistance and mechanical properties of polypropylene composite materials, enabling it to more effectively resist external scratches and stress concentration, and delay crack expansion.
Smart Images

Figure CN119119637B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PP plastics, in particular to a toughened and scratch-resistant polypropylene composite material. Background Art
[0002] Polypropylene (PP for short) is a semi-crystalline thermoplastic made from propylene through addition polymerization. The following is a detailed introduction to polypropylene materials:
[0003] Polypropylene material is usually a white waxy material, transparent and light in appearance, and also in colorless translucent solid form; the density is about 0.89~0.91g / cm³, the melting point is 164~170℃, softens at around 155℃, and the operating temperature range is -30~140℃. Polypropylene material has high impact resistance and mechanical strength, and is resistant to corrosion by a variety of organic solvents and acids and alkalis.
[0004] Polypropylene materials have a wide range of applications, including:
[0005] 1. Woven products: such as plastic woven bags, tarpaulins and ropes, etc., mainly used for packaging of grain, fertilizers and cement.
[0006] 2. Injection molded products: used in small household appliances, daily necessities, toys, washing machines, automobiles and turnover boxes.
[0007] 3. Film products: mainly include BOPP, CPP, ordinary packaging films and microporous films, etc., which are widely used in packaging, electrical engineering, electronic appliances and other fields.
[0008] 4. Fiber products: Polypropylene fiber made from polypropylene is increasingly used in the three major fields of decoration, industry, and clothing.
[0009] 5. Pipes: Polypropylene pipes are resistant to high temperatures, easy to connect (hot-melt, electric-melt, pipe connection), and recyclable. They are mainly used in building water supply systems, heating systems, farmland water delivery systems, and chemical pipeline systems.
[0010] With the growth of the global economy and the acceleration of industrialization, the performance requirements for polypropylene are constantly increasing, especially in some special fields, where high requirements are placed on the scratch resistance of polypropylene. However, the scratch resistance of existing polypropylene materials is relatively poor, which limits its use.
[0011] Therefore, the present invention solves the corresponding problems by providing a toughened and scratch-resistant polypropylene composite material. Summary of the invention
[0012] The purpose of the present invention is to provide a toughened scratch-resistant polypropylene composite material to solve the deficiencies in the prior art.
[0013] The technical solution adopted by the present invention is as follows:
[0014] A toughened and scratch-resistant polypropylene composite material comprises the following components in parts by weight:
[0015] 75-80 parts of polypropylene resin, 7.5-8 parts of maleic anhydride grafted polyethylene, 6-10 parts of modified nano silicon carbide, 1-2 parts of organic silane coupling agent, 15-20 parts of inorganic filler, 1-2 parts of antioxidant, 1-3 parts of stearic acid, 3-5 parts of elastomer, 1-1.6 parts of nano zinc oxide;
[0016] Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1;
[0017] Among them, the particle size of nano zinc oxide is 30-40nm.
[0018] As a further technical solution: the modified nano-silicon carbide preparation method is:
[0019] First, prepare the modifier solution:
[0020] Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution.
[0021] Among them, the stirring speed is 500r / min;
[0022] Add nano silicon carbide and modifier solution to a vacuum reactor in sequence, and then evacuate the reactor, adjust the temperature in the vacuum reactor to 75-80°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano silicon carbide.
[0023] As a further technical solution: the mixing ratio of alginate, tannin, boric acid and deionized water is: 6-8g: 2-3g: 6-9g: 300mL.
[0024] As a further technical solution: the alginate is sodium alginate or potassium alginate.
[0025] As a further technical solution: the mixing ratio of the nano silicon carbide and the modifier solution is 30-35g:220mL;
[0026] The vacuuming is to a vacuum degree of -0.012MPa;
[0027] The drying temperature is 150°C and the drying time is 30 minutes.
[0028] As a further technical solution: the preparation method of maleic anhydride grafted polyethylene is:
[0029] Weigh respectively: maleic anhydride, nano-silica, polyethylene resin;
[0030] The mixing mass ratios of maleic anhydride, nano-silicon dioxide and polyethylene resin are 5-6:1-3:20-22 respectively;
[0031] The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin;
[0032] The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours.
[0033] Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
[0034] As a further technical solution: the melt flow rate of the polyethylene is 2.5 g / 10 min;
[0035] The parameters of the twin-screw extruder are set as follows:
[0036] The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
[0037] As a further technical solution: the organic silane coupling agent is vinyltrimethoxysilane.
[0038] As a further technical solution: the elastomer is a mixture of EPDM rubber and nitrile rubber;
[0039] Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:1.
[0040] As a further technical solution: the inorganic filler is nano calcium carbonate;
[0041] The antioxidant is a phosphite antioxidant.
[0042] Beneficial effects:
[0043] The polypropylene composite material prepared by the invention not only has excellent mechanical properties, but also has excellent anti-scratch performance.
[0044] The present invention introduces modified nano silicon carbide into the polypropylene composite material. Due to its small particle size, large specific surface area, and increased physical and chemical defects on the surface, the chances of physical or chemical bonding between these nano particles and polymer chains are increased, making it difficult for the molecular chains to slide and break, thereby enhancing the rigidity of the matrix. This increase in rigidity helps to resist the generation of external scratches, thereby improving the scratch resistance of the material.
[0045] Directly introducing nano silicon carbide into the polypropylene composite material can improve the scratch resistance of the polypropylene composite material to a certain extent. However, due to the aggregation effect of nano silicon carbide, the dispersion in the polypropylene composite material is relatively poor, resulting in incomplete function. Therefore, the present invention can greatly improve the dispersion and compatibility of the modified nano silicon carbide in the polypropylene composite material by functional modification of the nano silicon carbide. The good dispersion ensures that the modified nano silicon carbide particles are evenly distributed in the polypropylene, avoiding the occurrence of agglomeration, and greatly improving the mechanical properties and scratch resistance of the polypropylene composite material. The modified nano silicon carbide after the modification treatment also helps to form a stronger interface interaction between the modified nano silicon carbide and the polypropylene due to the enhanced compatibility.
[0046] The addition of modified nano-silicon carbide can not only enhance the rigidity and surface hardness of the polypropylene composite material, but also improve the toughness of the polypropylene composite material to a certain extent. The improvement of the toughness of the polypropylene composite material means that the polypropylene composite material can better absorb and dissipate energy when subjected to external forces, thereby effectively reducing stress concentration and crack propagation, thereby greatly improving the scratch resistance of the polypropylene composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 It is a statistical diagram of Shore hardness D of each group in the embodiment. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The following are specific embodiments
[0050] Example 1
[0051] A toughened and scratch-resistant polypropylene composite material comprises the following components in parts by weight:
[0052] 75 parts of polypropylene resin, 7.5 parts of maleic anhydride grafted polyethylene, 6 parts of modified nano silicon carbide, 1 part of organic silane coupling agent, 15 parts of inorganic filler, 1 part of antioxidant, 1 part of stearic acid, 3 parts of elastomer, 1 part of nano zinc oxide;
[0053] Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1;
[0054] Among them, the particle size of nano zinc oxide is 30nm.
[0055] The preparation method of modified nano silicon carbide is:
[0056] First, prepare the modifier solution:
[0057] Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution.
[0058] Among them, the stirring speed is 500r / min;
[0059] Add nano-silicon carbide and modifier solution to a vacuum reactor in sequence, and then evacuate the reactor. Adjust the temperature in the vacuum reactor to 75°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano-silicon carbide.
[0060] The mixing ratio of alginate, tannin, boric acid and deionized water is: 6g:2g:6g:300mL.
[0061] Alginate is sodium alginate or potassium alginate.
[0062] The mixing ratio of nano silicon carbide and modifier solution is 30g:220mL;
[0063] The vacuuming is to a vacuum degree of -0.012MPa;
[0064] The drying temperature is 150°C and the drying time is 30 minutes.
[0065] The preparation method of maleic anhydride grafted polyethylene is as follows:
[0066] Weigh respectively: maleic anhydride, nano-silica, polyethylene resin;
[0067] The mixing mass ratio of maleic anhydride, nano-silica and polyethylene resin is 5:1:20 respectively;
[0068] The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin;
[0069] The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours.
[0070] Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
[0071] The melt flow rate of polyethylene is 2.5 g / 10 min;
[0072] The parameters of the twin-screw extruder are set as follows:
[0073] The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
[0074] The organic silane coupling agent is vinyltrimethoxysilane.
[0075] The elastomer is a mixture of EPDM and nitrile rubber;
[0076] Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:1.
[0077] The inorganic filler is nano calcium carbonate;
[0078] The antioxidant is a phosphite antioxidant.
[0079] Example 2
[0080] A toughened and scratch-resistant polypropylene composite material comprises the following components in parts by weight:
[0081] 76 parts of polypropylene resin, 7.6 parts of maleic anhydride grafted polyethylene, 8 parts of modified nano silicon carbide, 1.5 parts of organic silane coupling agent, 18 parts of inorganic filler, 1.2 parts of antioxidant, 2 parts of stearic acid, 3.5 parts of elastomer, 1.2 parts of nano zinc oxide;
[0082] Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1;
[0083] Among them, the particle size of nano zinc oxide is 30nm.
[0084] The preparation method of modified nano silicon carbide is:
[0085] First, prepare the modifier solution:
[0086] Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution.
[0087] Among them, the stirring speed is 500r / min;
[0088] Add nano-silicon carbide and modifier solution to a vacuum reactor in sequence, and then evacuate the reactor. Adjust the temperature in the vacuum reactor to 78°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano-silicon carbide.
[0089] The mixing ratio of alginate, tannin, boric acid and deionized water is: 7g:2.5g:8g:300mL.
[0090] Alginate is sodium alginate or potassium alginate.
[0091] The mixing ratio of nano silicon carbide and modifier solution is 32g:220mL;
[0092] The vacuuming is to a vacuum degree of -0.012MPa;
[0093] The drying temperature is 150°C and the drying time is 30 minutes.
[0094] The preparation method of maleic anhydride grafted polyethylene is as follows:
[0095] Weigh respectively: maleic anhydride, nano-silica, polyethylene resin;
[0096] Among them, the mixing mass ratios of maleic anhydride, nano-silica and polyethylene resin are 5.5:2:21 respectively;
[0097] The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin;
[0098] The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours.
[0099] Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
[0100] The melt flow rate of polyethylene is 2.5 g / 10 min;
[0101] The parameters of the twin-screw extruder are set as follows:
[0102] The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
[0103] The organic silane coupling agent is vinyltrimethoxysilane.
[0104] The elastomer is a mixture of EPDM and nitrile rubber;
[0105] Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:1.
[0106] The inorganic filler is nano calcium carbonate;
[0107] The antioxidant is a phosphite antioxidant.
[0108] Example 3
[0109] A toughened and scratch-resistant polypropylene composite material comprises the following components in parts by weight:
[0110] 78 parts of polypropylene resin, 7.8 parts of maleic anhydride grafted polyethylene, 9 parts of modified nano silicon carbide, 1.5 parts of organic silane coupling agent, 17 parts of inorganic filler, 1.8 parts of antioxidant, 2 parts of stearic acid, 3-5 parts of elastomer, 1.6 parts of nano zinc oxide;
[0111] Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1;
[0112] Among them, the particle size of nano zinc oxide is 30nm.
[0113] The preparation method of modified nano silicon carbide is:
[0114] First, prepare the modifier solution:
[0115] Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution.
[0116] Among them, the stirring speed is 500r / min;
[0117] Add nano silicon carbide and modifier solution to a vacuum reactor in sequence, and then evacuate the reactor. Adjust the temperature in the vacuum reactor to 76°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano silicon carbide.
[0118] The mixing ratio of alginate, tannin, boric acid and deionized water is: 7g:2.5g:8g:300mL.
[0119] Alginate is sodium alginate or potassium alginate.
[0120] The mixing ratio of nano silicon carbide and modifier solution is 32g:220mL;
[0121] The vacuuming is to a vacuum degree of -0.012MPa;
[0122] The drying temperature is 150°C and the drying time is 30 minutes.
[0123] The preparation method of maleic anhydride grafted polyethylene is as follows:
[0124] Weigh respectively: maleic anhydride, nano-silica, polyethylene resin;
[0125] Among them, the mixing mass ratios of maleic anhydride, nano-silica and polyethylene resin are 5.5:2:21 respectively;
[0126] The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin;
[0127] The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours.
[0128] Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
[0129] The melt flow rate of polyethylene is 2.5 g / 10 min;
[0130] The parameters of the twin-screw extruder are set as follows:
[0131] The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
[0132] The organic silane coupling agent is vinyltrimethoxysilane.
[0133] The elastomer is a mixture of EPDM and nitrile rubber;
[0134] Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:1.
[0135] The inorganic filler is nano calcium carbonate;
[0136] The antioxidant is a phosphite antioxidant.
[0137] Example 4
[0138] A toughened and scratch-resistant polypropylene composite material comprises the following components in parts by weight:
[0139] 80 parts of polypropylene resin, 8 parts of maleic anhydride grafted polyethylene, 7 parts of modified nano silicon carbide, 2 parts of organic silane coupling agent, 20 parts of inorganic filler, 1.5 parts of antioxidant, 2 parts of stearic acid, 4 parts of elastomer, 1.4 parts of nano zinc oxide;
[0140] Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1;
[0141] Among them, the particle size of nano zinc oxide is 30nm.
[0142] The preparation method of modified nano silicon carbide is:
[0143] First, prepare the modifier solution:
[0144] Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution.
[0145] Among them, the stirring speed is 500r / min;
[0146] Add nano silicon carbide and modifier solution to a vacuum reactor in sequence, and then evacuate the reactor, adjust the temperature in the vacuum reactor to 75-80°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano silicon carbide.
[0147] The mixing ratio of alginate, tannin, boric acid and deionized water is: 7g:2.5g:8g:300mL.
[0148] Alginate is sodium alginate or potassium alginate.
[0149] The mixing ratio of nano silicon carbide and modifier solution is 32g:220mL;
[0150] The vacuuming is to a vacuum degree of -0.012MPa;
[0151] The drying temperature is 150°C and the drying time is 30 minutes.
[0152] The preparation method of maleic anhydride grafted polyethylene is as follows:
[0153] Weigh respectively: maleic anhydride, nano-silica, polyethylene resin;
[0154] The mixing mass ratios of maleic anhydride, nano-silica and polyethylene resin are 6:2:21 respectively;
[0155] The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin;
[0156] The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours.
[0157] Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
[0158] The melt flow rate of polyethylene is 2.5 g / 10 min;
[0159] The parameters of the twin-screw extruder are set as follows:
[0160] The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
[0161] The organic silane coupling agent is vinyltrimethoxysilane.
[0162] The elastomer is a mixture of EPDM and nitrile rubber;
[0163] Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:1.
[0164] The inorganic filler is nano calcium carbonate;
[0165] The antioxidant is a phosphite antioxidant.
[0166] Example 5
[0167] A toughened and scratch-resistant polypropylene composite material comprises the following components in parts by weight:
[0168] 80 parts of polypropylene resin, 8 parts of maleic anhydride grafted polyethylene, 10 parts of modified nano silicon carbide, 2 parts of organic silane coupling agent, 20 parts of inorganic filler, 2 parts of antioxidant, 3 parts of stearic acid, 5 parts of elastomer, 1.6 parts of nano zinc oxide;
[0169] Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1;
[0170] Among them, the particle size of nano zinc oxide is 30nm.
[0171] The preparation method of modified nano silicon carbide is:
[0172] First, prepare the modifier solution:
[0173] Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution.
[0174] Among them, the stirring speed is 500r / min;
[0175] Add nano silicon carbide and modifier solution to a vacuum reactor in sequence, and then evacuate the reactor. Adjust the temperature in the vacuum reactor to 80°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano silicon carbide.
[0176] The mixing ratio of alginate, tannin, boric acid and deionized water is: 8g:3g:9g:300mL.
[0177] Alginate is sodium alginate or potassium alginate.
[0178] The mixing ratio of nano silicon carbide and modifier solution is 35g:220mL;
[0179] The vacuuming is to a vacuum degree of -0.012MPa;
[0180] The drying temperature is 150°C and the drying time is 30 minutes.
[0181] The preparation method of maleic anhydride grafted polyethylene is as follows:
[0182] Weigh respectively: maleic anhydride, nano-silica, polyethylene resin;
[0183] The mixing mass ratios of maleic anhydride, nano-silica and polyethylene resin are 6:3:22 respectively;
[0184] The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin;
[0185] The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours.
[0186] Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
[0187] The melt flow rate of polyethylene is 2.5 g / 10 min;
[0188] The parameters of the twin-screw extruder are set as follows:
[0189] The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
[0190] The organic silane coupling agent is vinyltrimethoxysilane.
[0191] The elastomer is a mixture of EPDM and nitrile rubber;
[0192] Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:1.
[0193] The inorganic filler is nano calcium carbonate;
[0194] The antioxidant is a phosphite antioxidant.
[0195] Comparative Example 1:
[0196] Based on the technical solution of Example 1, maleic anhydride grafted polyethylene is not added, and the rest of the technical solutions remain unchanged.
[0197] Comparative Example 2:
[0198] Based on the technical solution of Example 1, modified nano-silicon carbide is not added, and the rest of the technical solutions remain unchanged.
[0199] test:
[0200] Scratch resistance test:
[0201] The samples of the embodiment and the comparative example were tested according to GMW16488-A, with a needle diameter of 1 mm and a needle pressure of 10 N. The whiteness value difference (dL) before and after the test was tested; 10 samples in each group were averaged:
[0202] Table 1
[0203]
[0204] It can be seen from Table 1 that the polypropylene composite material prepared by the present invention has excellent scratch resistance.
[0205] Shore D hardness test: According to ISO7619-1:2015, the examples and comparative examples were tested, 10 samples in each group, and the average value was taken:
[0206] Table 2
[0207]
[0208] It can be seen from Table 2 that the surface hardness of the polypropylene composite plastic prepared by the present invention is relatively high.
[0209] Izod notched impact strength test:
[0210] The samples of the embodiment and the comparative example were tested according to ISO180-1e / A-2011 at a test temperature of 23°C:
[0211] Table 3
[0212]
[0213] It can be seen from Table 3 that the polypropylene composite plastic prepared by the present invention has excellent impact toughness.
[0214] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. A toughened and scratch-resistant polypropylene composite material, characterized in that: The following ingredients are included by weight: 75-80 parts of polypropylene resin, 7.5-8 parts of maleic anhydride grafted polyethylene, 6-10 parts of modified nano silicon carbide, 1-2 parts of organic silane coupling agent, 15-20 parts of inorganic filler, 1-2 parts of antioxidant, 1-3 parts of stearic acid, 3-5 parts of elastomer, 1-1.6 parts of nano zinc oxide; Wherein, the weight ratio of polypropylene resin to maleic anhydride grafted polyethylene is 10:1; Among them, the particle size of nano zinc oxide is 30-40nm; The modified nano-silicon carbide preparation method is: First, prepare the modifier solution: Alginate, tannin and boric acid were added to deionized water in sequence, the temperature was adjusted to 80°C, the mixture was stirred for 40 minutes, and then cooled to room temperature to obtain a modifier solution. Among them, the stirring speed is 500r / min; Add nano silicon carbide and modifier solution to a vacuum reactor in sequence, evacuate the reactor, adjust the temperature in the vacuum reactor to 75-80°C, keep the reactor warm for 2 hours, then discharge the material, cool it naturally to room temperature, filter it, wash it to neutrality, add it to a drying oven for drying, and obtain modified nano silicon carbide; The maleic anhydride grafted polyethylene preparation method is: Weigh respectively: maleic anhydride, nano-silica, polyethylene resin; The mixing mass ratios of maleic anhydride, nano-silicon dioxide and polyethylene resin are 5-6:1-3:20-22 respectively; The maleic anhydride, nano-silica and polyethylene resin are dried respectively to obtain dried maleic anhydride, nano-silica and polyethylene resin; The drying process is carried out in a drying oven at a temperature of 80°C for 4 hours. Maleic anhydride, nano-silicon dioxide and polyethylene are sequentially added into a twin-screw extruder, and after melting, extrusion and granulation in the twin-screw extruder, the desired maleic anhydride grafted polyethylene is obtained.
2. The toughened scratch-resistant polypropylene composite material according to claim 1, characterized in that: The mixing ratio of the alginate, tannin, boric acid and deionized water is: 6-8g: 2-3g: 6-9g: 300mL.
3. The toughened scratch-resistant polypropylene composite material according to claim 2, characterized in that: The alginate is sodium alginate or potassium alginate.
4. The toughened scratch-resistant polypropylene composite material according to claim 1, characterized in that: The mixing ratio of the nano silicon carbide and the modifier solution is 30-35 g: 220 mL; The vacuuming is to a vacuum degree of -0.012MPa; The drying temperature is 150°C and the drying time is 30 minutes.
5. The toughened scratch-resistant polypropylene composite material according to claim 1, characterized in that: The melt flow rate of the polyethylene is 2.5 g / 10 min; The parameters of the twin-screw extruder are set as follows: The temperature of zone 1 is 180℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 190℃, the temperature of zone 4 is 200℃, the temperature of zone 5 is 210℃, and the main engine speed is 250r / min.
6. The toughened scratch-resistant polypropylene composite material according to claim 1, characterized in that: The organic silane coupling agent is vinyltrimethoxysilane.
7. The toughened scratch-resistant polypropylene composite material according to claim 1, characterized in that: The elastomer is a mixture of EPDM rubber and nitrile rubber; Among them, the mixing mass ratio of EPDM rubber and nitrile rubber is 2:
1.
8. The toughened scratch-resistant polypropylene composite material according to claim 1, characterized in that: The inorganic filler is nano calcium carbonate; The antioxidant is a phosphite antioxidant.
Citation Information
Patent Citations
Wear-resistant and scraping-resistant injection-molding-grade PC / ABS alloy material and preparing method thereof
CN105623233A
Spinning method for preparing silicon carbide nanowires / alginic acid composite fiber
CN108950730A